Advances in audio and speech signal processing technologies and applications - Perez-Meana, Hector 1954-.; Gale Group (Hershey, Penn. Idea Group Pub., 2007)
Provides a comprehensive approach to signal processing tools regarding the enhancement, recognition, and protection of speech and audio signals. Offers researchers and practitioners the information they need to develop and implement efficient signal processing algorithms in the enhancement field.
Electronic reproduction.
Keywords: Sound -- Recording and reproducing; Signal processing -- Digital techniques; Speech processing systems; Electronic books; Signal processing -- Equipment and supplies; Automatic speech recognition